Death before birth: understanding, informing and supporting the choices made by people who have experienced miscarriage, termination and stillbirth 2017 - Littlemore, Jeannette (UK Data Service, 2019)
Anonymised transcripts of interviews with (1) professionals working in the funerary industry (funeral directors, bereavement service managers, and officers at national funeral care institutions), (2) bereavement care providers in hospitals within NHS England, (3) support workers at the Stillbirth and Neonatal Death Charity (Sands), Antenatal Results and Choices (ARC) and the Miscarriage Association (MA), (4) people (and partners of people) who have experienced a miscarriage, a stillbirth, or termination due to fetal anomaly. We also conducted focus group meetings with people (and partners of people) who have experienced a miscarriage, a stillbirth, or a termination due to fetal anomaly. We propose a socio-legal, linguistic study of how people in England who have experienced miscarriage, termination, and stillbirth reach decisions concerning the disposal of the remains of pregnancy, how their perceptions of the law impact on their decision-making, and how they communicate their experiences and choices to those who are there to support them. The project engages with an important and large-scale social issue: it is estimated that approximately 1 in 5 known pregnancies end in miscarriage, 1 in every 200 births is a stillbirth, and 2,000 terminations for reasons of fetal anomaly are performed in the UK each year. The study seeks to replace the social and legal uncertainty surrounding the question of what to do with the remains of pregnancy by engaging stakeholders with a view to producing evidence-led policy and practice. English law is not straightforward when it comes to definitions about the remains of pregnancy: in legal terms, the remains occupy a mid-way category somewhere between person and human tissue. Not surprisingly, those affected often lack knowledge of the legal options for the disposal of the remains. The disposal of the remains of pregnancy has been the subject of increased levels of media controversy and public scrutiny in the last 12 months. In the wake of these scandals, and in recognition of the need for national guidance in this area, the Human Tissue Authority (HTA) recently published guidelines for the disposal of the remains of pregnancy (25 March 2015). A key aspect of our investigation will assess how these guidelines are interpreted in practice by professionals (such as midwives and funeral directors) and how this shapes the way in which options are presented to the bereaved. We will also examine whether the guidelines take sufficient account of the views, experiences and needs of the bereaved. Our findings will inform the HTA's revision of the guidelines, and in doing so, we aim to contribute to improved care pathways for those experiencing pregnancy loss. The end of a pregnancy may be felt as a form of bereavement, one that usually involves complex emotions that are difficult to articulate. Linguistics research has demonstrated that metaphor is prevalent in the language used when people are communicating about emotionally charged, life-changing experiences. Furthermore, when people face bereavement through miscarriage, termination, and stillbirth, it can be difficult to organise a 'conventional' funeral, so people create their own, drawing on a selection of metaphors. This project will accordingly pay careful attention not just to what the bereaved and those who support them say, but how they express themselves through words and actions. In particular, it will explore how support workers and their clients reach for metaphor as a way of exploring options and expressing the inexpressible. By interviewing the bereaved and their support workers, we aim to provide guidance to agencies like Miscarriage Association (MA), the Stillbirth and Neonatal Death Charity (SANDS), and the Antenatal Results and Choices charity (ARC) in order to help them improve their communications with their clients. We will work together to produce material for their websites and will provide briefing documents for training sessions for staff. Beyond these immediate aims, we hope that by working directly with these agencies as our partners, our research results will contribute to the raising of public awareness about the options for the disposal of the remains of pregnancy, and enable productive debate about, and improvement of, those options.